PENGARUH MODEL PEMBELAJARAN KOOPERATIF TEAMS GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR SIWA MATA PELAJARAN MATEMATIKA KELAS III SD NEGERI 066039 MEDAN MARELAN - Septiani Simbolon, Sri; Patri Janson Silaban; Irmina Pinem; Frikson Joni Purba; Jhonas Dongoran (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The researcher aims to determine the Effect of the Team Games Tournament (TGT) Cooperative Learning Model on Student Learning Outcomes in Mathematics Subjects of Class III of SDN 066039 Medan Marelan in the 2024/2025 Academic Year. This study uses a quantitative method with a One- group Pretest-Posttest research design. The sample used was in class III totaling 26 students. The results of this study indicate that the average pretest score of students was 51.53, which is in the less category and increased to 79,15 in the posttest, which is in the good category. It can be said that the level of success of student learning outcomes has increased as evidenced by the results of the correlation calculation obtained. The results of the correlation coefficient test obtained rcount (0.800) ≥ rtable (0.3739). Furthermore, the hypothesis test compares the tcount value ≥ ttable. The value of tcount = 6,543 while ttable = 2.064 because tcount ≥ ttable (6,543 ≥ 2.064) then Ha is accepted and Ho is rejected. Through the test, it can be concluded that there is a significant positive influence between the Teams Games Tournament learning model (X) on student learning outcomes (Y).